The Impact of Corporate Volunteerism on Organisational Identity and Organisational Identification: The Perspective of Community Groups and Internal Stakeholders - Lau, Ying Hung (2007)
The current study seeks to uncover the process underlying the renegotiation process of organisational identity orientation, a framework proposed by Brickson (2005), as well as the change on the level of organisational identification in relation to corporate volunteerism, from the perspective of internal stakeholders and community groups.